Simulation and Manufacturing of Low Loss PCB Structures with Additional Electromagnetic Field in Air - Sepaintner, Felix; Scharl, Andreas; Röhrl, Franz Xaver; Bogner, Werner; Zorn, Stefan (IEEE MTT-S International Microwave Workshop Series on Advanced Materials and Processes for RF and THz Applications (IMWS-AMP), 2019)
This paper presents a new method to produce different kinds of RF waveguides with reduced attenuation on low cost PCB substrates. First, microstrip (MS) and grounded coplanar waveguides (GCPW) are characterized by considering rough conductors in CST Microwave Studio. Next, laminate is partially removed, to increase the electromagnetic field ratio in air. Accordingly, the dielectric losses are reduced and the electrical length is decreased. These conductors are produced by using a CO 2 laserdrilling machine to remove the undesired substrate. The RF performance (DC to 100 GHz) of these waveguides is compared to transmission lines manufactured in conventional PCB technology. Finally, different kinds of simulated and produced microstrip filters are shown and fabrication tolerances are compared to those produced in standard technology.<br
Keywords: low loss transmission lines; reduced tolerances; microstrip filters; sequential pre etching (SPE); wet-chemical etching; low cost PCB substrate